2008
DOI: 10.3382/ps.2007-00057
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Growth on Broiler Carcasses Stored at Different Temperatures After Air- or Water-Chilling

Abstract: Poultry meat has a high risk of contamination during its processing. Storage temperature, type of packaging, and types and numbers of psychrotrophic bacteria are the major factors determining the spoilage of poultry meat. Before packaging, poultry carcasses are chilled by air or water currents in commercial slaughterhouses. The packaging material and methods are other factors influencing the spoilage of poultry meat. Although unpackaged carcasses had lower production costs, they were found to contain high numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…At this point, there was no difference in psychrotrophic counts between AC and WC, but AC had a lower mesophilic count. These results are similar to those reported by Tuncer and Sireli [25], who concluded that the AC was superior to WC in terms of pathogen growth, though they did not speci cally investigate the spoilage bacteria described in the current study. Additionally, after the 7-day dark storage period the AC microbial community was much more diverse than the WC community, which was dominated by Pseudomonadaceae.…”
Section: Discussionsupporting
confidence: 92%
“…At this point, there was no difference in psychrotrophic counts between AC and WC, but AC had a lower mesophilic count. These results are similar to those reported by Tuncer and Sireli [25], who concluded that the AC was superior to WC in terms of pathogen growth, though they did not speci cally investigate the spoilage bacteria described in the current study. Additionally, after the 7-day dark storage period the AC microbial community was much more diverse than the WC community, which was dominated by Pseudomonadaceae.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that the type of chicken meat was a greater influence than the storage temperatures on bacterial communities. It was assumed that whole chicken (with skin) could be contaminated from feathers, feces, and soil, so that it might harbor different microbial populations than chicken breast ( Russell, 2009 ; Tuncer and Sireli, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Barnes and Thornley (1966) reported that the bacteria on broiler meat immediately after processing consisted of Micrococci (50%), gram‐positive rods (14%), Flavobacteria (14%), Enterobacteriaceae (8%), Pseudomonas (2%), Acinetobacter (7%), and unidentified organisms (5%) (Charles and others 2006). Davies and Board (1998) also found Pseudomonas , Acinetobacter , Achromobacter ,and Brochothrix thermosphacta after processing (Tuncer and Sireli 2008). …”
Section: Discussionmentioning
confidence: 98%